Photoselective vaporization of the prostate for treating benign prostatic hyperplasia. (September 2011) - Chughtai, Bilal; Te, Alexis
Benign prostatic hyperplasia (BPH) commonly occurs in older men. Traditionally, the gold standard for treatment of BPH has been the electrocautery-based transurethral resection of the prostate (TURP). However, TURP is associated with several complications and side effects. Therefore, there is an interest in a number of emerging minimally invasive therapies as alterative treatment options. Advancements in laser technology have led to the introduction of photoselective vaporization of the prostate (PVP) using the GreenLight™ laser (American Medical Systems, MN, USA). PVP uses a 532-nm laser to remove obstructive prostatic tissue. The laser energy is selectively absorbed by hemoglobin in the prostate tissue and results in tissue destruction. The GreenLight PVP laser system has gone through several evolutions from the original 60-W laser to the most recent 180-W GreenLight XPS™ system with MoXy™ Fiber. With the increasing use of GreenLight to treat BPH, there is a need to review the evidence regarding its use. We review the clinical implications of using GreenLight laser therapy for the treatment of BPH.